Molecular Characterization of Carbendazim Resistance of Plant Pathogen (Bipolaris oryzae) - Gomathinayagam, S.; Balasubramanian, N.; Shanmugaiah, V.; Rekha, M.; Manoharan, P. T.; Lalithakumari, D. (IntechOpen, 2011)
None